Validación biológica de la técnica de extracción a campo de estradiol fecal en el gato doméstico: reporte preliminar - Risso A. (2010)
The objective of this article was to biologically validate the ¨field method¨ for estradiol fecal extraction in domestic felids by a comparative study of samples obtained in different stages of the estrous cycle. A total at of 40 fecal samples from 7 postpubertal female cats were included. The samples were collected in the estrous (n=22) and interestrous (n=18) stages (defined by behavior and vaginal cytology) during 12 months. The "field extraction method" was carried out and then 17? estradiol was measured by radiommunoassay. Fecal estradiol concentration ranged from de 926 to 33320 pg/g wet weight. Mean ± SEM in estrous and interestrous samples were 11814±2171 pg/g and 3238±474 pg/g (p < 0.01), respectively. Longitudinal observation of estradiol values clearly indicated that peaks coincided with cytological and behavioral estrus.\n